Determination of ion recombination and polarity effect correction factors for a plane-parallel ionization Bragg peak chamber under proton and carbon ion pencil beams - Mirandola, Alfredo; Mairani, Andrea (Physics in medicine and biology, 2019)
Within the dosimetric characterization of particle beams, laterally-integrated depth-dose-distributions (IDDs) are measured and provided to the treatment planning system (TPS) for beam modeling or used as a benchmark for Monte Carlo (MC) simulations. The purpose of this work is the evaluation, in terms of ion recombination and polarity effect, of the dosimetric correction to be applied to proton and carbon ion curves as a function of linear energy transfer (LET). LET was calculated with a MC code for selected IDDs. Several regions of Bragg peak (BP) curve were investigated. The charge was measured with the plane-parallel BP-ionization chamber mounted in the Peakfinder as a field detector, by delivering a fixed number of particles at the maximum flux. The dose rate dependence was evaluated for different flux levels. The chamber was connected to an electrometer and exposed to un-scanned pencil beams. For each measurement the chamber was supplied with ±400, +200, +100 V. Recombination and polarity correction factors were then calculated as a function of depth and LET in water. Three energies representative of the clinical range were investigated for both particle types. The corrected IDDs (IDD k s) were then compared against MC. Recombination correction factors were LET and energy dependent, ranging from 1.000 to 1.040 (±0.5%) for carbon ions, while nearly negligible for protons. Moreover, no corrections need to be applied due to polarity effect being <0.5% along the whole IDDs for both particle types. IDD k s showed a better agreement than uncorrected curves when compared to MC, with a reduction of the mean absolute variation from 1.2% to 0.9%. The aforementioned correction factors were estimated and applied along the IDDs, showing an improved agreement against MC. Results confirmed that corrections are not negligible for carbon ions, particularly around the BP region.
Gesehen am 04.07.2019